Teacher training process - Frisancho León, Augusto (2014)
This paper deals with teacher training. Discusses some definitions on this process and also have their particular characteristics, emphasizing one: to be an ongoing activity. The authors argue that teacher training is one of the best indicators to assess the improvement of education and that it also plays an important role in building the identity of teachers. They argue that the professional development plan must be animated by an emancipatory interest, in support of a change of mentality, personality, into the role of teacher as a freelancer and not one that reproduces the given. In a second step, is analyzed the process of initial training, it is this crucial stage in the training of teachers. It lays the foundation for the necessary and required personality as teaching that the teacher must necessarily acquire. Are described three orientations of initial training: the academic or perennialist, the rational-technique and the based practice. Finally, is analyzed the continuing permanent education, which is what takes place during the teaching practice and the term ranging from initial training to the teacher retirement stage. Five models are proposed training.